A Study on the Piscifauna of Gandhisagar Reservoir with Particular Reference to the Abundance of Commercial Varieties of Fish* - K.N., Kartha; K.S., Rao (Fishery Technology, 2025)
A study of the pisdfauna of Gandhisagar reservolr, Chambal river, Madhya Pradesh, during 1985-86, has revealed the presence of 41 fish species belonging to 5 orders, 14 families and 28 genera. Commerdally important species were Catla catla, Labeo rohita, Cirrhinus mrigela, followed by Labeo calbasu, Aorichthys aor, A. seenghala, Wallago attu, Ompok bimaculatus and Silonia silondia. Relative dominance of exotic species, Calla cutla and labeo rohita, ln the landings contributing nearly 98% (1985-86) has confirmed that these species have successfully established themselve ln the ecosystem of Gandhisagar. Comparison with the results of prelmpoundment surveys has indicated a reduction in the species diversity, with the establishment of reservoir.